The role of Yogurt in improving the quality of the American diet and meeting dietary guidelines. (March 2014) - Webb, Densie; Donovan, Sharon M; Meydani, Simin Nikbin
<x xml:space="preserve">Abstract</x> The Dietary Guidelines for Americans (DGA) recommend three daily servings of low‐ or nonfat dairy products, yet two‐thirds of individuals in the United States do not meet that goal. Including low‐ or nonfat yogurt as part of an overall healthful diet can be a positive step toward meeting the DGA recommendations. Yogurt naturally contains calcium and potassium, and some products are fortified with vitamin D. All of these nutrients were identified in the DGA as "nutrients of concern, " because typical intake falls far short of recommended intakes. Yogurt can also be an excellent source of high‐quality protein, which promotes satiety, helps in maintaining a healthy body weight, and aids muscle and bone growth. In addition, yogurt is low in sodium and contributes 1.0% or less of added sugars to the diets of most individuals in the United States; however, 90% of children and adults consume less than 8 ounces (1 cup) of yogurt per week. Thus, consuming 1 serving of yogurt per day would help to meet the DGA‐recommended dairy servings and would provide nutrients of concern.